Slow-mode rarefaction and compression fronts in the Hermean magnetosphere: From MESSENGER insights to future BepiColombo observations - Varela Rodríguez, Jacobo; Pantellini, F. (Astronomy & Astrophysics, 2023)
Context. Standing slow-mode rarefaction and compression front structures may appear in the Mercury magnetosheath under particular solar wind conditions. Aims. The aim of the study is to identify the wind conditions required for the formation of slow-mode structures (SMS) in the Mercury magnetosphere by comparing MESSENGER magnetometer data and magnetohydrodynamics simulations. Methods. We used the magnetohydrodynamics code PLUTO in spherical coordinates to reproduce the interaction of the solar wind with the Mercury magnetosphere. First, the optimal wind conditions for the SMS formation were identified with respect to the orientation of the interplanetary magnetic field (IMF) and dynamic pressure. Next, the magnetic field calculated in the simulations along the MESSENGER trajectory was compared to MESSENGER magnetometer data to identify tracers of the satellite encounter with the SMS. Results. Optimal wind conditions for the formation of SMS require that the IMF is oriented in the northward or radial directions. The MESSENGER orbit on 8th September 2011 takes place during wind conditions that are close to the optimal configuration for SMS formation near the north pole, leading to the possible intersection of the satellite trajectory with the SMS. MESSENGER magnetometer data show a rather strong decrease in the magnetic field module after the satellite crossed nearby the compression front that is observed in the simulation, providing indirect evidence of the SMS. This work was supported by the project 2019-T1/AMB-13648 founded by the Comunidad de Madrid and the European Commission’s Seventh Framework Programme (FP7/2007-2013) under the grant agreement SHOCK (project number 284515). Data available on request from the authors.